Pathological changes in gills, liver and kidney of Goldfish (Carassius auratus) when exposed to clove oil using the fish anaesthesia delivery system - Nordin, Hanisah (2018)
The pathological changes in gills, liver and kidney of Goldfish(Carassius auratus) following exposure to clove oil using the fish anaesthesia delivery system were studied. In this study, the duration of maintenance stage during surgery in Goldfish were 5 minutes (G1), 15 minutes (G2) and 30 minutes (G3) using 50 mg/L clove oil while the Goldfish in group 4 (G4) served as the control. The gills, kidney and liver were sampled from all groups for macroscopic and microscopic evaluation. The results revealed that although there was no gross changes observed, histopathological alterations of gills characterised by epithelial swelling, epithelial lifting, oedema and dilatation of blood vessels were present in fish in G1, G2 and G3 with the highest lesion scoring was observed in G3. In addition, results showed that clove oil has no harmful effect towards kidney and liver both macroscopically and microscopically. In conclusion, this study verified that the duration of exposure to clove oil for 5 minutes and 15 minutes are relatively safer in Goldfish as less injurious effects were observed in gills and the fish anaesthesia delivery system using clove oil can provide optimum anaesthesia to conduct surgical procedures in Goldfish.Thus, this study suggests that the duration of exposure to clove oil for 5 minutes and 15 minutes is relatively safer as there were less pathological effects on the gills. In conclusion, the result from this study revealed that clove oil can be used as anaesthesia for surgery related to Goldfish by using the fish anaesthesia delivery system.